«LIBROS ÚTILES A LAS CIENCIAS Y A LAS ARTES»: BIBLIOTECAS DE OFICIOS EN LA GALICIA DEL SIGLO XIX - Santiago Prego González (Cuadernos de Ilustración y Romanticismo)
Many libraries were established in Galicia and in the rest of Spain during the nineteenth century for vocational education and to train workers in crafts and professions. These libraries belonged in many cases to private institutions established during the Enlightenment that had played an important role in the economic development of the country. This paper analyses the characteristics of these institutions in Galicia, a region that experienced deep political, economic and social transformation in nineteenthcentury Spain and which witnessed interesting cultural initiatives aimed at disseminating knowledge.